Applications of Technology to Psychometric Evaluation - Burga León, Andrés Alberto (2019)
The objective of this work is to point out the importance and applicability of technology, especially the use of computers, in psychometric evaluation. To this end, three topics are presented, in an introductory manner, which, in the author's opinion, are some of the most outstanding. Specifically, the central aspects of items improved with technology, item banks and computerized adaptive tests are presented. As for technology-enhanced items, emphasis is placed on their importance for broadening the representativeness and fidelity with which a construct is measured, pointing out different printed and internet resources that can be consulted to see more examples of this type of items. When dealing with the issue of the item bank, the role that they currently play is highlighted, which goes far beyond being an organized store of items, to become a true computer system that allows the items to be elaborated, reviewed and applied. Finally, the main aspects of an adaptive computerized test are presented. Based on a bank of items, it allows, in real time, to estimate the measurement of a latent feature and apply appropriate items according to said estimate. Reference is also made to an alternative linked to free software, which allows the implementation of an adaptive computerized test.